Kamisama kiss. Vol. 6 - Suzuki, Julietta (Shojo beat manga., 2011)
"Every year, kami from all over Japan gather in Izumo for a sort of divine convention. One of Mikage's friends comes to the shrine to invite Nanami to the retreat, but it turns out most of the other kami and Tomoe don't want her to go. Can Nanami prove she's kami enough to attend-- or does she even want to bother?"--Publisher's web site.